Influence of consumption of high oleic sunflower oil on the biosynthesis of fatty acids in the liver of rats - A. Levitsky; B. Egorov; A. Lapinskaya; I. Selivanskaya; V. Velichko (Kazimierz Wielki University, 2022)
Background. To determine the effect of consumption of high-oleic sunflower oil on the content and biosynthesis of energy and polyunsaturated (PUFA) fatty acids in rat liver lipids. Methods. Rats received a semi-synthetic fat-free diet in which 5 % or 15 % starch was replaced with high oleic sunflower oil. One group of rats received a diet with 5 % regular (high linoleic) sunflower oil. The duration of feeding was 30 days. Liver lipids were divided into three fractions: neutral lipids, phospholipids and free fatty acids, in which the fatty acid composition was determined by gas chromatography. The "activity" of fatty acid synthase, palmitic acid elongase, and stearyl-CoA desaturase (SCD18) was determined by the ratio of fatty acid content. Results. It was found that the largest amount (60-80 %) of fatty acids in liver lipids are energy (C16:0 + C16:1 + C18:0 + C18:1). PUFA account for 10-30% of all fatty acids, and they are also found in the liver lipids of rats fed a free-fat diet (FFD). Fatty diets reduce the "activity" of synthase, but increase the "activity" of elongase and desaturase. A diet with high linoleic sunflower oil reduces the content of ω-3 PUFA in lipids, while a diet with high oleic sunflower oil increases it dose-dependently. Fatty diets containing high oleic sunflower oil dose-dependently reduce the "activity" of palmitic acid desaturase (SCD16). Consumption of high linoleic sunflower oil sharply increases the ratio of ω-6/ω-3 PUFA in liver lipids, while diets with high oleic oil reduce it dose-dependently.